A smart card (MyKad) and fingerprint authentication for e-voting system - Ismail, Rosli; Zulkifli, N. N.; Magiman, M. M.; M. R., Mohd Saufi (IJERT, 2022)
The issue of voting still poses a significant threat to voters' personal safety and the integrity of the election. Smart cards have gotten a lot of attention because they are secure and can be used for a wide range of services. Fingerprint identification is the oldest method and has been used successfully in various applications and is one of the most essential identifiers of humans. This paper proposes a model of validation process using fingerprint on the smart card for an e- voting system. In most elections held across the world, voters cast their ballots on paper rather than utilizing biometric technology. The existing voting system contains security flaws, such as issues with verifying the identity of voters. In the proposed model, a voters identity can be proved immediately by scanning his/her fingerprint on the scanner and improving voting security to eliminate the possibility of ballot duplication. Therefore, with this proposed model, voters will be able to cast their votes using their fingerprints rather than traditional paper-based and manual identity checking. As e-voting continues to evolve, this paper contributes to voters' validation process and knowledge to eliminate the possibility of ballot duplication and lying about voter's identity.